2009
DOI: 10.1111/j.1469-1809.2009.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between HERC2, OCA2 and MC1R May Influence Human Pigmentation Phenotype

Abstract: SummaryHuman pigmentation is a polygenic trait which may be shaped by different kinds of gene-gene interactions. Recent studies have revealed that interactive effects between HERC2 and OCA2 may be responsible for blue eye colour determination in humans. Here we performed a population association study, examining important polymorphisms within the HERC2 and OCA2 genes. Furthermore, pooling these results with genotyping data for MC1R, ASIP and SLC45A2 obtained for the same population sample we also analysed pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 41 publications
4
88
0
13
Order By: Relevance
“…Similar results were observed for already published male and female eye colour frequency data in Icelandic and Dutch populations [8] but not in Australian [9] and Polish populations [10]. Martinez-Cadenas and co-workers [1] suggested that the prediction success of the IrisPlex model and other models used to predict eye colour phenotypes from DNA genotypes may be improved by including gender as a factor.…”
Section: Introductionsupporting
confidence: 86%
“…Similar results were observed for already published male and female eye colour frequency data in Icelandic and Dutch populations [8] but not in Australian [9] and Polish populations [10]. Martinez-Cadenas and co-workers [1] suggested that the prediction success of the IrisPlex model and other models used to predict eye colour phenotypes from DNA genotypes may be improved by including gender as a factor.…”
Section: Introductionsupporting
confidence: 86%
“…16,26,32,39 Analysis of the HERC2-OCA2 region enables prediction of extreme (blue or brown) eye colours from genetic data with a reasonably high accuracy and has already been applied in real cases concerning identification of human remains. 40,41 Several other genes have been found to contribute to a lesser degree to the continuous variation in iris colour from light blue through intermediate (green and hazel) to dark brown, which is observed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the rs12913832 position additionally recessive categorisation was applied and this was chosen for reporting as more appropriate and giving clearer results, which is also supported by our previous study. 26 In the case of the MC1R gene, polymorphisms were divided into two groups: the high penetrance variants coded as 'R' (N29insA, V84E (rs1805006), R151C (rs1805007), R142H (rs11547464), R160W (rs1805008), D294H (rs1805009) and Y152OCH), and low penetrance variants coded as 'r' (V60L (rs1805005), V92M (rs2228479), I155T (rs1110400) and R163Q (rs885479)). For high penetrance variants ('R'), three states were considered, assuming the existence of major function mutations; that is, 0¼no 'R' variant carriers, 1¼one 'R' variant carrier and 2¼two 'R' variant carriers.…”
Section: Statistical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most strongly associated variant, rs12913832, shows the homozygous A allele in the Iceman's genome (coverage depth ×31), which is associated with brown eye colour in over 80% of cases even when regarded alone 30 . Branicki et al 31 defined a haplotype of five SNPs as predictor: rs4778138, rs4778241, rs7495174, rs12913832 and rs916977. The Iceman's haplotype (for which TTTTC and TTTTT were addressed together as the last SNP is a clear heterozygote) in the Branicki study encompassed 46 individuals, 8 of which were blue eyed, the residual 38 having a non-blue eye colour.…”
Section: Snp Analysismentioning
confidence: 99%